The similarity of the structure of DSM-IV criteria for major depression in depressed women from China, the United States and Europe. Issue 9 (July 2015) - Kendler, K. S.; Aggen, S. H.; Li, Y.; Lewis, C. M.; Breen, G.; Boomsma, D. I.; Bot, M.; Penninx, B. W. J. H.; Flint, J.
<x content-type="archive" xml:space="preserve">Abstract</x> Background Do DSM-IV diagnostic criteria for major depression (MD) in Chinese and Western women perform in a similar manner? Method The CONVERGE study included interview-based assessments of women of Han Chinese descent with treated recurrent MD. Using Mplus software, we investigated the overall degree of between-sample measurement invariance (MI) for DSM-IV diagnostic criteria for MD in the CONVERGE sample and samples selected from four major Western studies from the USA and Europe matched to the inclusion criteria of CONVERGE. These analyses were performed one pair at a time. We then compared the results from CONVERGE paired with Western samples to those obtained when examining levels of MI between pairs of the Western samples. Results Assuming a single factor model for the nine diagnostic criteria for MD, the level of MI based on global fit indexes observed between the CONVERGE and the four Western samples was very similar to that seen between the Western samples. Comparable results were obtained when using a two-factor structure for MI testing when applied to the 14 diagnostic criteria for MD disaggregated for weight, appetite, sleep, and psychomotor changes. Conclusions Despite differences in language, ethnicity and culture, DSM criteria for MD perform similarly in Chinese women with recurrent MD and comparable subjects from the USA and Europe. The DSM criteria for MD may assess depressive symptoms that are relatively insensitive to cultural and ethnic differences. These results support efforts to compare findings from depressed patients in China and Western countries.